A Systematic Review of Youth Participatory Action Research (YPAR) in the United States: Methodologies, Youth Outcomes, and Future Directions. (December 2018) - Anyon, Yolanda; Bender, Kimberly; Kennedy, Heather; Dechants, Jonah
Objectives . To use a systematic review methodology to describe the state of the youth participatory action research (YPAR) literature and synthesize findings about the youth outcomes reported in these studies. Methods . We screened and coded studies using a process consistent with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Of the 3, 724 articles found in the database search, 67 reports of 63 distinct studies were included in the final sample. These reports were coded for reports of YPAR principles and project characteristics, study methods, and reported youth outcomes. Results . The YPAR literature comprises predominantly qualitative studies, with only two randomized trials. The most common outcomes associated with participation in YPAR were those related to agency and leadership (75.0%), followed by academic or career (55.8%), social (36.5%), interpersonal (34.6%), and cognitive (23.1%) outcomes. Conclusions . This systematic review provides emerging evidence of the skills and competencies youth may develop through YPAR and offers methodological recommendations for future research that can provide greater evidence of causality.